Designed landscapes of the central Northamptonshire gentry: c. 1770 - c. 1840 - Radley, Stephen G (2024)
The designed landscapes of the gentry have frequently been studied as examples of the landscapes of a county, designer or period and have rarely been treated as distinctively gentry landscapes. The wealth, size of landholding and role the gentry played in local governance often resulted in an intimate relationship expressed socially and spatially in the village and parish in which the Hall and designed landscape were located which has also been generally ignored. This thesis is a close study of four designed landscapes which aims to understand the form and function of improvements considered or made and the relationship between the designed landscapes and the village and parish of which they were a part.